2022
DOI: 10.7554/elife.68648
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoproteomics of ATR signaling in mouse testes

Abstract: The phosphatidylinositol 3′ kinase (PI3K)‐related kinase ATR is crucial for mammalian meiosis. ATR promotes meiotic progression by coordinating key events in DNA repair, meiotic sex chromosome inactivation (MSCI), and checkpoint-dependent quality control during meiotic prophase I. Despite its central roles in meiosis, the ATR-dependent meiotic signaling network remains largely unknown. Here, we used phosphoproteomics to define ATR signaling events in testes from mice following chemical and genetic ablation of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(35 citation statements)
references
References 80 publications
8
27
0
Order By: Relevance
“…We found that the γH2AX domain disappeared from the XY chromatin in H1T-positive mid-pachytene spermatocytes following treatment with AZ20, but not in testes from untreated mice (Fig. 8b), consistent with another independent study using the same condition 59 . To examine the maintenance of MSCI in this mouse model, we prepared chromosome spreads using cell suspensions.…”
Section: Ddr-mediated Initiation Of Msci In the Absence Of H3k9me3supporting
confidence: 90%
See 2 more Smart Citations
“…We found that the γH2AX domain disappeared from the XY chromatin in H1T-positive mid-pachytene spermatocytes following treatment with AZ20, but not in testes from untreated mice (Fig. 8b), consistent with another independent study using the same condition 59 . To examine the maintenance of MSCI in this mouse model, we prepared chromosome spreads using cell suspensions.…”
Section: Ddr-mediated Initiation Of Msci In the Absence Of H3k9me3supporting
confidence: 90%
“…A recent study with AZ20, which was originally developed for chemotherapy, used an in vivo mouse model and a testicular organ culture model to show that ATR is required to complete meiotic recombination 20 . Another study used AZ20 for phosphoproteomics of ATR signaling in mouse testes using an in vivo mouse model 59 . In our study, we instead focused on treating mouse spermatocytes ex vivo with two different ATR inhibitors to specifically address the function of ATR in MSCI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Proteins eluted from anti-HA beads were processed for mass spectrometry analysis following a previously described protocol that includes reduction, alkylation, precipitation, and digestion by trypsin over-night 88 . Peptides were then desalted, dried 89 and labelled with TMT following a protocol described previously 90 . Briefly, the dried peptides were resuspended in 50 mM HEPES, and labeled with 100 µg of TMT sixplex Isobaric Label Reagents (Thermo Scientific) using 3 TMT channels for each sample ( Wild-type and FANCJ-HA ).…”
Section: Methodsmentioning
confidence: 99%
“…These challenges can only be overcome by utilizing MS-based proteomics ( Humphrey et al, 2018 ; Savage and Zhang, 2020 ; Liu et al, 2021 ). The field of phosphoproteomics has emerged greatly in the last decade ( Lundby et al, 2013 ; Sharma et al, 2014 ; Alam et al, 2015 ; Riley and Coon, 2016 ; Steger et al, 2016 ; Tan et al, 2017 ; Kuzmanov et al, 2020a ; Wu et al, 2020 ; Sims et al, 2022 ). It has contributed significantly to biological research.…”
Section: Development Of Cardiac Fibrosismentioning
confidence: 99%